2020
DOI: 10.5152/tjg.2020.18631
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics and clinical risk factors of Helicobacter pylori infection and antibiotic resistance in the Eastern Black Sea region of Turkey

Abstract: Stem cells for pancreatitis 425 Gastric injury and bacterial overgrowth 433 The effect of visceral fat on SMA configuration 451 Antiplatelet agents in ulcerative colitis 459 Differentiation of BMSCs into intestinal ce 466 GERDOFF ® efficacy in patients with GERD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
3
9
1
Order By: Relevance
“…In the cases in which atrophy could be evaluated as pathologic, the frequency of atrophy was 0.9%. As expected, the frequency of atrophy was significantly higher at older ages (median (IQR) 62 (17), 53 (24), p=0.022, respectively). There was no significant difference between genders in terms of the frequency of atrophy (p > 0.05).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In the cases in which atrophy could be evaluated as pathologic, the frequency of atrophy was 0.9%. As expected, the frequency of atrophy was significantly higher at older ages (median (IQR) 62 (17), 53 (24), p=0.022, respectively). There was no significant difference between genders in terms of the frequency of atrophy (p > 0.05).…”
Section: Resultssupporting
confidence: 75%
“…While Kösekli found the frequency of HP to be 71% (11) 13). In the 2010 study by Erkut et al, the frequency of HP in the Trabzon region was reported to be 40.4% (17). Interestingly, the frequency of HP in our study was 27.7%, which was lower than that reported in the literature.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition, clarithromycin, metronidazole, levofloxacin, tetracycline, and amoxicillin resistance rates range between 18-34%, 28.7-56%, 0-22%, 0-10%, and 0-14%, respectively, in different regions of the world [13,16,[39][40][41], and are 3. [27,[44][45][46]. In a previous study carried out in Bursa province, which is also the location of the present study, the rates of clarithromycin, metronidazole, tetracycline, and amoxicillin resistance were found to be 41.9%, 41.9%, 3.2%, and 3.2%, respectively [14] ( Table 3).…”
Section: Discussionsupporting
confidence: 53%
“…In a community-based survey conducted in 4663 adults in Turkey, the prevalence of H. pylori was determined as 82.5% with the UBT [21]. The prevalence of H. pylori in dyspeptic patients is reported to range between 17-34% in developed countries [22,23], 75.6-86% in developing countries [24,25], and 59.6-71.3% in Turkey [26,27]. In the present study, the prevalence of H. pylori (75.6%) was higher than the prevalence reported for developed countries and similar to that reported for developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…According to the difference and the difference of TC, TG, HDL-C, LDL-C, ALT, BUN, Hcy, hs-CRP, HSP60, ICAM-1, and GLU to determine whether it is HP virus, various logistic regression analysis results show that patients with coronary heart disease HP disease was associated with TC, TG, HDL-C, HSP60, and ICAM-1 ( P < 0.05), suggesting that TC, HSP60, and ICAM-1 were elevated, and TG and HDL-C reduction might have an impact on HP disease in CHD patients. This result may be due to the fact that after Hp infection, the disorder of lipid metabolism can aggravate the inflammatory reaction of vascular wall, resulting in the corresponding increase of the level of various inflammatory factors, and the level of inflammatory factors is positively correlated with HP infection [ 20 , 21 ]. ICAM-1 is an important immune active molecule in the body, which plays a role in the immune process, especially when the body is invaded by inflammation and tumor.…”
Section: Analysis Of Helicobacter Pylori Infection...mentioning
confidence: 99%